2008
DOI: 10.1159/000126499
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Cognitively Impaired Not Demented to Alzheimer’s Disease: An Analysis of Changes in Functional Abilities in a Dementia Clinic Cohort

Abstract: Background: Patients with cognitive impairment no dementia (CIND) are at an increased risk of progression to Alzheimer’s disease (AD). Whether subtle impairments in functional or social abilities at the CIND stage can predict progression to AD is not yet fully determined. We evaluated whether impairments on the Disability Assessment for Dementia (DAD) and Functional Rating Scale (FRS) can predict progression to AD. Methods: We examined 70 patients with CIND from the ACCORD cohort having complete DAD and FRS ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
2
15
0
1
Order By: Relevance
“…Previous studies found a later decline for BADL than for IADL in AD or in mild cognitive impairment, and this was also true for the REAL cohort [22,31] . Other studies showed a rapid decline in BADL for AD patients with severe cognitive decline [32] .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Previous studies found a later decline for BADL than for IADL in AD or in mild cognitive impairment, and this was also true for the REAL cohort [22,31] . Other studies showed a rapid decline in BADL for AD patients with severe cognitive decline [32] .…”
Section: Discussionsupporting
confidence: 60%
“…The fact that in the REAL cohort the MMSE range was wide (10-26 at inclusion) permitted us to perform the present study, because several studies underline a marked link between cognitive impairment and functional decline in AD patients [20][21][22] . The finding of a pattern of loss of ADL depends on the score for each activity, according to the scale used.…”
Section: Discussionmentioning
confidence: 99%
“…Existing measures used to quantify treatment effects in mild-tomoderate AD may not be sufficiently sensitive to capture the more subtle cognitive and functional impairments that persons with MCI experience. Some functional impairment may begin during the predementia (MCI) phase of AD [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Impairments in higher order cADLs, such as financial capacity, social planning, complex verbal facility, and other skills and activities related to executive function, may be among the earliest deficits in persons with MCI [4,6,7]. Furthermore, people with MCI may note deficits in some activities, such as reading, long before the deficit is observable to others [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the diagnostic criteria for mild cognitive impairment (MCI) include ''essentially intact'' functioning, whereas criteria for dementia require impaired daily functioning (American Psychiatric Association, 1994;Petersen et al, 2009). Many studies have found, however, that persons with MCI have difficulty with cognitively demanding activities like managing finances and medications and that these difficulties predict progression to dementia or, in fact, represent early Alzheimer's disease (AD; Allaire et al, 2009;Farias et al, 2006;Hsiung et al, 2008;Okonkwo et al, 2006;Peres et al, 2006). Despite the pivotal role of functional status for case definition, no valid criteria exist to make diagnostic distinctions.…”
mentioning
confidence: 99%